Regioselective Monoarylation of 2-Phenylbenzimidazole via Ruthenium-Catalyzed C–H Bond Functionalization - Kobayashi, Yasuyuki; Kashiwa, Mitsuhiro; Sonoda, Motohiro; Kirihata, Mitsunori; Tanimori, Shinji (Synthesis, 2014)
The highly regioselective monoarylation of 1-methyl-2-phenyl-1H-benzimidazole has been demonstrated. The reaction of 1-methyl-2-phenyl-1H-benzimidazole with 4-iodoanisole provided 2-(4′-methoxybiphenyl-2-yl)-1-methyl-1H-benzimidazole as the sole product in 96% isolated yield in the presence of [RuCl2(p-cymene)]2 and triphenylphosphine as precatalysts. A series of novel 2-(biphenyl-2-yl)benzimidazoles have been synthesized in good to excellent yields.
Keywords: C–H bond activation; benzimidazole; arylation; ruthenium catalyst; directing group